The Context Meaning of Deixis in Soundtracks Lyric of the Greatest Showman Movie - Baiatun Nisa; Arinta Geby Asi; Sulhizah Wulan Sari (Metathesis: Journal of English Language, Literature, and Teaching, 2020)
Deixis is one of the important studies in pragmatics. It is a word or phrase that can refer to a person, place, or time in the speakers' utterance. Usually, each deixis has a different function.  That function relies on the context of deixis both implicitly and explicitly. Then, the objective of this research is to find the types of deixis and divulge the function which is applied in the speaker utterance. The writers used the descriptive qualitative method to analyze deixis in the two soundtracks lyric of The Greatest Showman movie, they are the greatest show and This is me. The results of the analysis found that there are five types of deixis in the two lyrics; person deixis, spatial deixis, temporal deixis, discourse deixis, and social deixis. The functions showed that deixis provides the information and gives a reference to the deixis word. This analysis is important to understand the speaker's intends in the song by the use of context deixis.